Sunburn as a Cause of Unexpected Neutrophilia in a Healthy Pregnant Woman - Robert Harper (Hindawi Limited, 2018)
Background. Neutrophilia has a broad differential diagnosis and represents a systemic response to an infection or other inflammatory pathologies. Case. A 31-year-old woman, Gravida 3, Para 2 at 28 weeks of gestation, presented to the day assessment unit following routine blood tests that showed an unexpected marked neutrophilia. The underlying cause of the neutrophilia was sunburn. The sunburn recovered and her neutrophil count spontaneously normalised. Conclusion. Clinicians can add sunburn to the broad differential diagnosis of neutrophilia.